Nordic Experiences in Pan-nationalisms A Reappraisal and Comparison, 1840-1940 - Hemstad, Ruth; Stadius, Peter (Nordic Studies in a Global Context, 2023)
This book seeks to reassess and shed new light on pan-nationalisms in general and on Scandinavianism/Nordism in particular, by seeing them as possible futures and as interconnected ideas and practices across and beyond Europe. An actor- and practice-oriented approach is applied at the expense of more essentialist categorisations of what pan-nationalism is, or is not, to underline both the synchronic and diachronic diversity of various pan-national movements. A range of expert international scholars discuss encounters, transfers, similarities and differences among pan-movements in Norden and Europe based on a broad empirical material, focusing on Scandinavianism/Nordism, pan-Slavism, pan-Turanism, pan-Germanism and Greater Netherlandism, and the position of Britishness in Great Britain. This book will be of key interest to scholars and students of nationalism, European history, European studies and Scandinavian studies, history, social science, political geography, civil society and literary studies.